Using Resources as Synchronizers to Manage Mobile Process Adaptation - Bottoni, Paolo; De Rosa, Fabio; Mecella, Massimo (Electronic Communications of the EASST, 2009)
Process management in Mobile Ad-hoc NETworks (MANETs) has to deal with different types of tasks and resources. Teams can be formed with specific goals, such as recognition of a damaged area for disaster assessment, where each member of a team is assigned some task to be performed according to some policy. However, in real situations, it is possible that task assignments and policies have to be revised due to different causes. In addition to typical causes for dynamic changes in adaptive workflows, mobility introduces some specific problems, e.g. the need for new connectivity-maintaining tasks, or reassignment of tasks originally for members who have become unreachable, or who have no sufficient resources to complete the original plan. As these modifications occur dynamically, it is difficult to manage them through hard-coded programs. Rather, we propose the use of a rule-based formalism, expressed in terms of multi-set rewriting. This supports a resource-centered view, in which both data-dependencies between tasks and plan-dependent ordering of tasks are expressed as production and consumption of resources of different types. In turn, rules are themselves seen as resources, so that they are prone to the same rewriting process, in order to redefine process schemas. The paper illustrates these notions and formalisms, and shows some cases of their application.